2021
DOI: 10.1177/00469580211056213
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemotherapy in Early Triple-Negative Breast Cancer: A Pairwise and Network Meta-Analysis of Pathological Complete Response

Abstract: We performed a pairwise and network meta-analysis to compare pathological complete response (pCR) among neoadjuvant chemotherapy in patients with triple-negative breast cancer. We searched PubMed for randomized clinical trials between January 1, 2000 and December 1, 2020. Abstracts from meetings were also searched. A frequentist random-effect model was applied to compare pCR and toxicities. The P-score was used to rank treatment effects. Nineteen trials with 16 treatments and 7794 patients were included. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…According to the results of the current study, our control group had a higher proportion of node-positive patients (68.6%) than other studies, such as CALGB 40603 (58%) [ 41 ], BrighTNess (43%) [ 42 ], and KEYNOTE-522 (44.1%) [ 43 ], which might result in lower pCR rate in our control group. Nonetheless, the pCR rate fell within the reported range for patients with TNBC who received NAC, according to a meta-analysis (14%-53.4%) [ 44 ].…”
Section: Discussionmentioning
confidence: 97%
“…According to the results of the current study, our control group had a higher proportion of node-positive patients (68.6%) than other studies, such as CALGB 40603 (58%) [ 41 ], BrighTNess (43%) [ 42 ], and KEYNOTE-522 (44.1%) [ 43 ], which might result in lower pCR rate in our control group. Nonetheless, the pCR rate fell within the reported range for patients with TNBC who received NAC, according to a meta-analysis (14%-53.4%) [ 44 ].…”
Section: Discussionmentioning
confidence: 97%
“…One meta-analysis showed that the pCR rate using this regimen was ∼40%. 2 Several meta-analyses have shown that addition of platinum to the standard regimen increases the rate of pCR and lengthens event-free survival (EFS) or disease-free survival (DFS). 1 , 3 Given the seriousness of cardiac toxicity induced by anthracycline, there is increasing interest in exploring anthracycline-free neoadjuvant or adjuvant chemotherapy regimens for treatment of TNBC.…”
Section: Introductionmentioning
confidence: 99%